An Initial Sketch of Malaysia Incorporated as a Manifestation of Malaysian Authoritarian Corporatism - Mohd Kamal , Khairil Annuar b (Faculty of Economics and Business, 2012)
In this paper I attempt to conceptualize and describe the concept of Malaysia Incorporated as an element of Malaysia’s very own authoritarian corporatism. I will first think of Malaysia Inc by comparing similar ‘Incs’ in the UK, France, South Korea and Japan. I will also define Malaysia Inc according to the terms used the Government and I will sketch its evolution. After that I will provide a brief discuss and future research will be suggested. The main idea of this paper is that Malaysia Inc is not just a private-government partnership: it is a manifestation of what can be said to be a form of authoritarian corporatism. For now I will call this – the Malaysian Authoritarian Corporatism. I will conclude with my future plans of research in this area.